HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DENGAN MODEL KOOPERATIF THINK PAIR SHARE DI SEKOLAH DASAR - Andriansyah, Zul Alfa; Eliyasni, Rifda; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The purpose of this study is to describe the improvement of student learning outcomes in learning IPS Using Pembelajaran kooperatif Model Type Think Pair Share (TPS) in class V SD Negeri 29 Purus Padang City. Research subjects were teachers (practitioners) and 18 students, The result of this research shows an excalation from cycle I to cycle II on : a) planning of 8,9%, b) implementation, teacher aspect and student aspects of 21,45%, and    c) student learning outcomes of 21,35%. It can be concluded that used Cooperative Learning Model Type Think Pair Share can improve students achievement in learning social study of elementary school.